The influence of nature and culture in the formation of traditional food at Lenggong Valley, Perak - Abdul Raji, Mohd Nazri; Ab. Karim, Shahrim; Esa, Jamilah Hani (Penerbit Universiti Sains Malaysia, 2024)
Traditional food is a valuable asset inherited from one generation to another. The formation of this traditional food in specific district or country is influenced by various factors such as natural environment, cultural intermingling, political boundaries and local genius. As a result, the background and characteristic of traditional food can reflect the community’s origin, culture and identity. Despite that, research on the formation of traditional food is seemingly limited, particularly in the rural area. This phenomenon is due to the lack of appreciation to the traditional food among the community especially the young generation. Thus, this study aimed to understand the formation of traditional food in Lenggong Valley based on the influence of nature and culture factors. A qualitative research design was used in this study. The data was collected through semi structured interviews, and purposive sampling technique was employed by the researchers. A total of 10 informants were involved in this study comprised of Lenggong traditional food experts and entrepreneurs. In addition, snowball sampling technique was used to achieve data saturation. To validate the findings from semi structured interviews,participant observations were also executed by the researchers. Several places were visited such as traditional food restaurants, events and homestays to conduct the observations. Findings for this study have concluded into two themes namely, (1) Lenggong traditional food based on the availability of natural resources; and (2) the influence of culture diversity in the formation of Lenggong traditional food. This study explored the formation process of Lenggong traditional food that is influenced by the natural environment and culture diversity, in which the influence of both, explains the ingenuity of the past people in crafting various types of food which can still be tasted until today. Findings for this study imply the current generation to preserve and sustain this intangible heritage for the next generations to come. Beside inheritance, the uniqueness and differences of Lenggong’s traditional food connotes a potential that can also be benefited as a tourist attraction.